1994
DOI: 10.1136/jmg.31.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Parental origin of the X chromosome in a patient with a Robertsonian translocation and Turner's syndrome.

Abstract: We report on a proband with both a Robertsonian translocation and Turner's syndrome. Study of the parental origin of the X chromosome performed by microsatellite analysis indicates paternal origin of the X chromosome (Xpat). The present report deals with a new case of monosomy X combined with t(13;14). As the translocation was paternally inherited, we wanted to evaluate if the second aberration (XO) had the same origin. Simple dinucleotide sequence repeats have been shown to be highly polymorphic and useful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Laszlo et al (1984) reported a patient, her mother and sister, who all had a t(13;14). Krajinovic et al (1994) found that both X-chromosomes and the t(13;14) were paternally inherited in one of their patients. Silva et al (2006) reported a patient who had both translocation and X-chromosome that were demonstrated to be maternally inherited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laszlo et al (1984) reported a patient, her mother and sister, who all had a t(13;14). Krajinovic et al (1994) found that both X-chromosomes and the t(13;14) were paternally inherited in one of their patients. Silva et al (2006) reported a patient who had both translocation and X-chromosome that were demonstrated to be maternally inherited.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, four cases of monosomy X associated with balanced Robertsonian translocation t(13;14) (Laszlo et al, 1984;Salamanca et al, 1985;Krajinovic et al, 1994;Silva et al, 2006) and one previous case of Turner's syndrome with familial balanced translocation t(1;2) (q32;q21)mat (Kondo et al, 1979) have been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…Using high resolution banding, Ozkul et al (2002) found a TS infant with the karyotype 45X,t(1;2)(q41;p16), and one case of TS with familial balanced translocation t(1;2)(q32;q21)mat was described by Kondo et al (1979). Four other studies reported an association of X-monosomy with balanced Robertsonian translocation t(13;14) (Laszlo et al, 1984;Salamanca et al, 1985;Krajinovic et al, 1994;Silva et al, 2006). Recently, Djordjević et al (2010) showed a case of 45,X,t(1;9) (cen;cen) in combination with a r(X) mosaic karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Laszlo et al (1984) reported the case of a patient, his mother and sister, who all had a t(13;14), but found no evidence of an interchromosomal effect. Krajinovic et al (1994) found that both the X chromosome and the t(13;14) translocation in one of their patients were paternally inherited and thus demonstrated that the translocation had no effect on X chromosome non-disjunction. Kondo et al (1979) compared the expected and observed frequency of the 45,X karyotype combined with unrelated balanced translocations and concluded that there was no causal relationship between the two chromosomal abnormalities…”
Section: Introductionmentioning
confidence: 99%